The Role of the Sarva Dharma Ashram in Contributing to the Well-Being of Youth and Their Families in Welbedacht, South Africa - Gurcharan, Yashna (Religions, 2021)
Faith-based organisations act as a powerful source of growth, empowerment and well-being for families in their milieu. This study used a qualitative research approach, specifically a case study design, to explore the role of the Sarva Dharma Ashram in contributing to the wellbeing of youth and their families in the Welbedacht community in South Africa. Three samples, which consisted of 24 participants, were purposively selected. These three samples were made up of the Board members of the Sarva Dharma Ashram, family members who are members of the Sarva Dharma Ashram and community members who live within the milieu of the Ashram. Semi-structured in-depth interviews and a focus group discussion were used to collect data. Following a thematic analysis of this data, the study found that the Sarva Dharma Ashram played a central role in empowering and enabling the wellbeing of disadvantaged family and community members. The ashram not only provided assistance when psychosocial or financial distress was encountered but also highlighted the spiritual support offered to families and other community members in order to transcend the socioeconomic ills they faced as a marginalised community.